Solar Water Pumping in Energy, Water and Food Nexus of Nepal - Ranabhat, Ramesh; Khadka, Sundar Bahadur (Journal of Advanced College of Engineering and Management, 2019)
Agricultural based country Nepal has sufficient arable land. Even though sufficient water sources for the irrigation, farmers are fully reliant on the monsoon. More over only about 18 percent of the total cultivated land receives year round irrigation. More than half of the population have less than 0.5 hectare with average land holding of 0.85 hectare. With this intensive care can give to their farm. But only a season they are cultivated their land. In this context about seventy one thousand tons of food deficit in the country annually. But rapidly declining costs and technology improvements encourage to adopt solar based systems for the irrigation projects. So that is interested to supplement their income through growing vegetables in commercial scale with changing crop pattern through irrigation. Integrated approach for Energy-Water-Food would be essential for development.